Editorial: How to prepare a scientific article for publication - Ramos, Armando Dias (2018)
Scientific production has never been as thoroughly examined/debated as nowadays.In the era of Computer Science and of shared information, the proliferation of scientific magazines online leads to a double control carried out on publications. We mustn’t neglect that the credibility of in line magazines is directly related to the quality and originality of the published scientific articles. On the other hand, there is a wider control over an article before it is published, checking thoroughly if it shows no plagiarism. The double-blind peer review becomes essential when allowing a scrutiny and the validation of the scientific articles intended to be published. To write an essay requires knowledge and appropriate techniques, otherwise we will not be producing a scientific article but a mere opinion piece. Throughout this editorial we draw some guidelines that could lead our readers, probable authors in the future, to an improvement in their research, writing and after publication.